Analisis kelayakan finansial usahatani manggis di Desa Sagalaherang, Kecamatan Sagalaherang, Kabupaten Subang - Febryane, Rimelke Rahmadea; Kundrat; Lily Sumarti; Burhanudin (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
Subang is one of the mangosteen production centers in West Java Province that conducts export activities. Laksana Barokah Farmer Group is a group that exports mangosteen even though farmers feel that the return on investment in mangosteen farming is uncertain. The purpose of this study was to determine the feasibility of mangosteen farming carried out by a farmer in the Laksana Barokah Farmer Group, Sagalaherang Village, Sagalaherang District, Subang Regency, and to determine the profit and payback period of mangosteen farmers. The research method used is the case study method, which determines the location and sample intentionally (purposive). The respondents selected were 1 farmer which has an existing mangosteen plant aged 30 years and a land area of 2 hectares. Data collection methods were carried out through observation, direct interviews, and literature studies. The results of the analysis show that mangosteen farming activities carried out by farmers in the Laksana Barokah Farmer Group in Sagalaherang Village are feasible to run and develop with the value of investment criteria, namely, R / C Ratio of 4.59; Net B/C Ratio of 12.04; Net Present Value (NPV) of Rp. 363,227,997; Internal Rate of Return (IRR) of 10%; and Payback Period (PP) for 9.04 years. What needs to be improved by other farmers in this area is to improve the production system through the application of Good Agricultural Practice (GAP) and renewing land certification every 2 years so that the selling value of mangosteen increases.